Cytoreductive nephrectomy in metastatic renal cell carcinoma - Dahm, Philipp; Ergun, Onuralp; Uhlig, Annemarie; Bellut, Laura; Risk, Michael C.; Lyon, Jennifer A.; Kunath, Frank (Cohrane Library, 2024)
Background: Nephrectomy is the surgical removal of all or part of a kidney. When the aim of nephrectomy is to reduce tumor burden in people with established metastatic disease, the procedure is called cytoreductive nephrectomy (CN). CN is typically combined with systemic anticancer therapy (SACT). SACT can be initiated before or immediately after the operation or deferred until radiological signs of disease progression. The benefits and harms of CN are controversial. Objectives: To assess the effects of cytoreductive nephrectomy combined with systemic anticancer therapy versus systemic anticancer therapy alone or watchful waiting in newly diagnosed metastatic renal cell carcinoma. Search methods: We performed a comprehensive search in the Cochrane Library, MEDLINE, Embase, Scopus, two trial registries, and other gray literature sources up to 1 March 2024. We applied no restrictions on publication language or status. Selection criteria: We included randomized controlled trials (RCTs) that evaluated SACT and CN versus SACT alone or watchful waiting. Data collection and analysis: Two review authors independently selected studies and extracted data. Primary outcomes were time to death from any cause and quality of life. Secondary outcomes were time to disease progression, treatment response, treatment-related mortality, discontinuation due to adverse events, and serious adverse events. We performed statistical analyses using a random-effects model. We rated the certainty of evidence using the GRADE approach. Main results: Our search identified 10 records of four unique RCTs that informed two comparisons. In this abstract, we focus on the results for the two primary outcomes. Cytoreductive nephrectomy plus systemic anticancer therapy versus systemic anticancer therapy alone. Three RCTs informed this comparison. Due to the considerable heterogeneity when pooling across these studies, we decided to present the results of the prespecified subgroup analysis by type of systemic agent. Cytoreductive nephrectomy plus interferon immunotherapy versus interferon immunotherapy alone. CN plus interferon immunotherapy compared with interferon immunotherapy alone probably increases time to death from any cause (hazard ratio [HR] 0.68, 95% confidence interval [CI] 0.51 to 0.89; I²= 0%; 2 studies, 326 participants; moderate-certainty evidence). Assuming 820 all-cause deaths at two years' follow-up per 1000 people who receive interferon immunotherapy alone, the effect estimate corresponds to 132 fewer all-cause deaths (237 fewer to 37 fewer) per 1000 people who receive CN plus interferon immunotherapy. We found no evidence to assess quality of life. Cytoreductive nephrectomy plus tyrosine kinase inhibitor therapy versus tyrosine kinase inhibitor therapy alone. We are very uncertain about the effect of CN plus tyrosine kinase inhibitor (TKI) therapy compared with TKI therapy alone on time to death from any cause (HR 1.11, 95% CI 0.90 to 1.37; 1 study, 450 participants; very low-certainty evidence). Assuming 574 all-cause deaths at two years' follow-up per 1000 people who receive TKI therapy alone, the effect estimate corresponds to 38 more all-cause deaths (38 fewer to 115 more) per 1000 people who receive CN plus TKI therapy. We found no evidence to assess quality of life. Immediate cytoreductive nephrectomy versus deferred cytoreductive nephrectomy. One study evaluated CN followed by TKI therapy (immediate CN) versus three cycles of TKI therapy followed by CN (deferred CN). Immediate CN compared with deferred CN may decrease time to death from any cause (HR 1.63, 95% CI 1.05 to 2.53; 1 study, 99 participants; low-certainty evidence). Assuming 620 all-cause deaths at two years' follow-up per 1000 people who receive deferred CN, the effect estimate corresponds to 173 more all-cause deaths (18 more to 294 more) per 1000 people who receive immediate CN. We found no evidence to assess quality of life. Authors' conclusions: CN plus SACT in the form of interferon immunotherapy versus SACT in the form of interferon immunotherapy alone probably increases time to death from any cause. However, we are very uncertain about the effect of CN plus SACT in the form of TKI therapy versus SACT in the form of TKI therapy alone on time to death from any cause. Immediate CN versus deferred CN may decrease time to death from any cause. We found no quality of life data for any of these three comparisons. We also found no evidence to inform any other comparisons, in particular those involving newer immunotherapy agents (programmed death receptor 1 [PD-1]/programmed death ligand 1 [PD-L1] immune checkpoint inhibitors), which have become the backbone of SACT for metastatic renal cell carcinoma. There is an urgent need for RCTs that explore the role of CN in the context of contemporary forms of systemic immunotherapy.
CRIS-Team Scopus Importer:2024-06-14